Patterns of structural change and manufacturing development - Haraguchi, Nobuya (UNIDO ViennaAT, 2015)
Provides emipirical insights. Presents the patterns of structural change for the entire economy, giving particular attention to changes in the amount of manufacturing value added and employment in the economy. Discusses the individual effects of the three majror factors of structural change proposed, namely income level, geographic and demographic conditions and other country-specific factors. Reviews the temporal aspect of structural change in manufacturing. Summarises the analyses of different explanatory factors of manufacturing structural change and illustrates how these factors are individually related to the patterns and country specifcities of manufacturing development.